Milwaukee Youngstar: Exploring the Racialized Experiences of African American Early Care and Education Providers - (:unkn) unknown (My University, 2018)
In 2010, the State of Wisconsin passed legislation to implement a program called YoungStar. YoungStar is a quality rating improvement system that is used to prevent fraud in the Wisconsin childcare subsidy program called Wisconsin Shares and to rate the quality of early care and education centers (ECECs) on a scale from one to five stars. Programs rated as two stars receive assistance from technical consultants to help programs to make improvements. The purpose of this study was to understand the experiences of African American early care and education providers (ECEPs) and their interactions with YoungStar technical consultants. This study also attempted to find out whether or not the ECEPs perceived that they had racialized experiences that affected their ability to make improvements in their programs. In relying upon questionnaires and one-on-one interviews with Milwaukee African American early care and education providers, the findings of this study suggests that the ECEPs previous racialized experiences with a governing agency affected their interactions with the technical consultants and that their interactions with the technical consultants may have affected the ECEPs abilities to improve their quality rating.
Keywords: critical race theory; racialization